More Unequal, But More Mobile? Earnings Inequality and Mobility in OECD Countries - Andrea Garnero; Alexander Hijzen; Sébastien Martin (Institute for the Study of Labor (IZA), 2016)
This paper provides comprehensive cross-country evidence on the relationship between earnings inequality and intra-generational mobility by simulating individual earnings and employment trajectories in the long-term using short panel data for 24 OECD countries. On average across countries, about 25% of earnings inequality in a given year evens out over the life cycle as a result of mobility. Moreover, mobility is not systematically higher in countries with more earnings inequality in general. However, a positive and statistically significant relationship is found only in the bottom of the distribution. This reflects the role of mobility between employment and unemployment and not that of mobility up and down the earnings ladder.
Keywords: E24; J30; J62; O57; 330; intra-generational mobility; life-time inequality; earnings-experience profiles; simulation